2014
DOI: 10.1016/j.neuroscience.2013.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidine dithiocarbamate attenuates surgery-induced neuroinflammation and cognitive dysfunction possibly via inhibition of nuclear factor κB

Abstract: Surgery induces learning and memory impairment. Neuroinflammation may contribute to this impairment. Nuclear factor κB (NF-κB) is an important transcription factor to regulate the expression of inflammatory cytokines. We hypothesize that inhibition of NF-κB by pyrrolidine dithiocarbamate (PDTC) reduces neuroinflammation and the impairment of learning and memory. To test this hypothesis, four-month old male Fischer 344 rats were subjected to right carotid exploration under propofol and buprenorphine anesthesia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
83
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 31 publications
(71 reference statements)
8
83
2
Order By: Relevance
“…It became clear that IFN, TNF-␣, members of the interleukin (IL) family, and other cytokine mediators are highly sensitive to experimental conditions that are related to critical illness. A partial listing with representative references includes sepsis (241,328), mechanical trauma (246), surgery (670,802), pneumonia (71,527), drug-induced organ failure (660), thermal injury (484,743), and peritonitis (36).…”
Section: A Cytokine Elevation In Critical Illnessmentioning
confidence: 99%
“…It became clear that IFN, TNF-␣, members of the interleukin (IL) family, and other cytokine mediators are highly sensitive to experimental conditions that are related to critical illness. A partial listing with representative references includes sepsis (241,328), mechanical trauma (246), surgery (670,802), pneumonia (71,527), drug-induced organ failure (660), thermal injury (484,743), and peritonitis (36).…”
Section: A Cytokine Elevation In Critical Illnessmentioning
confidence: 99%
“…Centrally administered renin and Ang-II are known to disrupt cognition possible mediated through AT1 receptors and documented to be associated with cholinergic system (Li et al 2014;Wayner et al 1993). Besides, Ang-II is also known to affect the production of COX-2 and other inflammatory pathways via NF-kB expression which plays crucial role in cognitive dysfunction (Zhang et al 2014). In the present study, combination of losartan with nimesulide significantly caused protection (on plus maze performance test and acetylcholinesterase activity) as compared to their effect alone indicating their possible synergistic like effect.…”
Section: Discussionmentioning
confidence: 99%
“…In order to explore the mechanisms responsible for the promotion of cytokine secretion induced by H. pylori infection of MSCs, the expression of NF-κB, one of several key signaling transducers involved in inflammation and cancer (23), was determined in H. pylori-infected MSCs. Western blotting revealed that the expression levels of NF-κB-p65 were significantly higher in hucMSCs that had been infected with H. pylori (Fig.…”
Section: H Pylori Enhances the Expression Of Certain Cytokines In Msmentioning
confidence: 99%